Termination interview - Grant, Lois- (North Adelaide : Video Communicators, 1900)
The good termination interview should make people feel: (a) approriate to leave (b) they get help and moral support for the future (c) more caring towards the organization (d) they leave for a better future
Keywords: Exit interviews